2008
DOI: 10.1159/000113012
|View full text |Cite
|
Sign up to set email alerts
|

Wilms’ Tumor in Children: An Overview

Abstract: Wilms’ tumor is the most frequently occurring renal tumor in children and is one of the most treatment-responsive tumors. A tumor-suppressor gene and other genetic abnormalities have been implicated in its etiology. In addition, patients with several congenital anomalies, such as Beckwith-Wiedemann syndrome, WAGR syndrome, and Denys-Drash syndrome, have an increased risk of Wilms’ tumor. Previously, a three-drug chemotherapy regimen with surgery and radiotherapy was used with patients in all stages. Now, patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0
8

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 119 publications
(66 reference statements)
2
32
0
8
Order By: Relevance
“…Wilms tumor is the most prevalent renal malignant tumor in children. But fortunately, it is also one of the most treatment-responsive tumors (reviewed in [88]). Thus, several therapeutic options are available to treat Wilms tumor successfully.…”
Section: S1p In Renal Disease Modelsmentioning
confidence: 99%
“…Wilms tumor is the most prevalent renal malignant tumor in children. But fortunately, it is also one of the most treatment-responsive tumors (reviewed in [88]). Thus, several therapeutic options are available to treat Wilms tumor successfully.…”
Section: S1p In Renal Disease Modelsmentioning
confidence: 99%
“…Kaval trombüs cerrahi öncesinde bilinmezse nefrektomi sırasında emboli ve mortaliteye neden olabilir (2) bun farklı tedavi yaklaşımı bulunmaktadır. Bu gruplar, Kuzey Amerika ülkelerini kapsayan Ulusal Wilms Tümörü Çalışma Grubu (National Wilms' Tumor Study Group (NWTSG) günümüzde Children's Oncology Group (COG)'un bir parçasıdır) ile Avrupa'da Société Internationale d'Oncologie Pédiatrique (SIOP)'dir (2,3) . Ülkemizde ise olgular Türk Pediatrik Onkoloji Grubu (TPOG) protokolüne göre sağaltıl-maktadır (4) .…”
Section: Wi̇lms Tümörüunclassified
“…This assertion can be corroborated by studies done in the sub-Saharan Africa by Ekense et al [2,3] which showed that Wilms' tumour is the most common childhood malignancy in Sub-Saharan Africa. Despite being a malignant tumour, a survival rate of over 90% is now seen today (compared to 30% in the thirties) and this is an evidence of the success of collaborative trials and the use of multimodal therapy [4][5][6]. Generally, childhood renal tumours are largely of embryonic origin, with rapidity of growth and a better response to therapy [1].…”
Section: Introductionmentioning
confidence: 99%
“…Generally, childhood renal tumours are largely of embryonic origin, with rapidity of growth and a better response to therapy [1]. Black children have a 2.5 times increased incidence over their white counterparts and the sex ratio is close to 1 [4]. Wilms' tumour is also associated with a number of recognised syndromes including WAGR, Beckwith-Wiedemann and Denys-Drash syndromes [1].…”
Section: Introductionmentioning
confidence: 99%